Strengthening Financial Performance Models through Local Evidence from the Rural Banking Sector - Arsana, I Ketut; Taufiqurahman, Cecep; Muslim, Ade Imam (International Ecsis Association, 2025)
Rural Banks (BPR) play a crucial role in supporting regional economic stability, yet limited studies have examined the local determinants of their profitability. This study aims to analyze the influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Operating Expense Ratio (OER) on the profitability (Return on Assets/ROA) of BPRs in Tangerang City. A quantitative research method was employed using secondary data from BPR financial statements published by the Financial Services Authority (OJK) for the period 2021–2023. The data were processed through descriptive statistics, classical assumption tests, and multiple regression analysis to evaluate both simultaneous and partial effects. The results show that CAR, NPL, and OER collectively have a significant effect on ROA. However, individually, only OER has a significant negative impact, while CAR and NPL do not exhibit direct influences on profitability. This finding highlights that operational efficiency, as reflected in OER, is the dominant factor shaping the financial performance of BPRs. Excessive operating costs reduce profitability, whereas strong capitalization and credit risk do not directly alter returns under the observed conditions. The implications of this research are twofold: first, BPR management must prioritize cost control strategies to enhance financial performance; second, regulators should design microprudential policies that align with the unique characteristics of rural banking institutions, thereby strengthening their contribution to regional economic development.